The application of supply chain analysis to the evaluation of the effectiveness of social service organizations = Zastosowanie analizy łańcucha dostaw dla oceny efektywności organizacji dostarczających usługi społeczne - Szołtysek, Jacek; Frąckiewicz-Wronka, Aldona (Zielona Góra: Faculty of Economics and Management Press)
The identification and analysis of value chains is a way to find the sources of an organization's in-/efficiency, and an opportunity to explore how an organization is managed. Having in mind that an "organization network" is a form similar, in its functioning, to a separate organization, one may, using the value chain concept, investigate the management of local activity programmes, as of the networks they are. The researched partnerships introduced a management innovation, in that the social service provision organizations were brought together to form one chain. [...]
Keywords: analiza łańcucha dostaw; usługi społeczne; efektywność; key success factors strategy; public organization; social services